Reading postwar British and Irish poetry - Thurston, Michael, 1965-; Alderman, Nigel (Chichester, West Sussex [U.K.] ; Hoboken [New Jersey] : Wiley-Blackwell, 2014)
"This essential guide helps readers gain a deeper comprehension of British and Irish poetry produced from 1945 to the present day"--
Introduction: "Postwar," "British," "Irish," and "Poetry" -- A Brief Historical Survey -- The Literary Landscape -- Histories of Forms -- Poetry of Place -- History and Historiography -- Varieties of the Long Poem -- Subject To, Subject Of -- Anthologies and Groups -- Epilogue: Beyond "British," and "Irish," and "Poetry."
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 1900-2099; English poetry -- 20th century -- History and criticism; English poetry -- 21st century -- History and criticism; English poetry -- Irish authors -- History and criticism; Poetics; Poetry -- Explication; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English poetry; English poetry -- Irish authors; Poetics; Poetry -- Explication; Electronic books; Criticism, interpretation, etc